Evaluasi Program Tahfidz Alqur’an Pondok Pesantren Sabilillah Pasuruan - Tarwichatul Jadidah; Parmujianto; Ahmad Kawakip (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Evaluation is an assessment process that compares the achievement of a program in the field with the standards that have been formulated. Studying the Qur'an, especially when memorizing the Qur'an, must use the right and clear method, and the most common among Quran memorizers is to use the talaqqi method. The purpose of the evaluation of the tahfidz program at the Sabilillah boarding school is to make improvements for the sustainability of the program. The method used in this study is a qualitative method. This research was conducted by collecting descriptive data and then analyzed qualitatively. The data collection method used is observation techniques and literature study. In the observation of researchers, this tahfidz program has obstacles that have an impact on the sustainability of student activities during memorization deposits. Researchers found indications in the form of no students who have successfully completed the memorization of 30 juz even though this program has been running for four and a half years. The evaluation used by the researcher is a type of comprehensive program evaluation that uses the CIPPO Evaluation Model. Regarding the many problems arising from the context and program of tahfidz deposits, further programs have been prepared, namely; Providing a routine schedule of